Nursing care for the patient after gastric resection due to cancer - Medak, Edyta; Ciechański, Aleksander; Niedzielski, Antoni (Journal of Education, Health and Sport, 2017)
Background:Gastric cancer (RZ) is the second leading cause of cancer in the world leading to death. Although each year the incidence of RZ is lower, it is still one of the highest in the group of most common malignancies. Due to the fact that cancer patients have similar symptoms to other gastrointestinal diseases, it is often detected at an advanced stage. This cancer can be located in different parts of the stomach and often has an unusual course. Surgical treatment of patients with RZ is most often associated with complete gastric excision and causes numerous ailments. Correct preparation of patients for surgery has a significant impact on therapeutic success. A nurse who carries a cancer patient is not only concerned with assessing his / her current state of health, executing medical orders, education on post-hospital leave, but also providing emotional support before surgery. The role of the nurse is also to provide the patient with the information needed during his stay in the ward [1, 2,3,16]. Purpose of the study: Evaluate the patient's treatment before complete removal of the stomach from cancer. Material and method: The study was conducted in the period from 17.09.2012 to 15.05.2013 in the group of 60 patients (35 men and 25 women) of the II Department and Clinic of General Surgery, Gastroenterology and Gastrointestinal Cancer of the Independent Public Clinical Hospital No. 1 in Lublin. Patients have been qualified for total abdominal surgery for cancer. The research tool was the author's questionnaire survey. The results of the study were statistically analyzed. Results: According to data obtained, more than half (60%) of patients presenting with gastric resection at the Clinic of General Surgery, Gastroenterology and Gastrointestinal Diseases of the Independent Public Clinical Hospital No. 1 in Lublin have a high level of care in this department. There was no case for the patient to underestimate nursing care. Conclusions: The majority of patients rated nursing care performed prior to surgery at a high level.